Transparent: When Legal Fictions and Judicial Imagination Make Facts Disappear, They Enforce Transphobic Discrimination - Hammer, Gail Anne (Columbia Journal of Gender and Law, 2015)
Kim is a transgender parent who was ordered to pay more in child support than she earned. When she could not pay, a court found her in contempt and put her in jail. In jail, she was dressed in a woman’s uniform, paraded through every part of the men’s population, and then held in solitary confinement in the wing for violent male offenders. Her story provides an example of how courts sometimes view legal fictions as more real than the facts of a person’s life. Legal fictions include presumptions, which are defined as “legal inference[s] or assumption[s] that a fact exists because of the known or proven existence of some other fact or group of facts.” When used appropriately, legal fictions can facilitate the law’s legitimate purposes. However, when facts contradict legal fictions, facts should be considered, in order to temper the potential for resulting irrationality and injustice. Legal fictions impact specific groups disproportionately. This is particularly true for those whose experiences are outside judges’ experiences. This Article gives an example of this disproportionate impact and recommends that courts consider discrimination in hiring as relevant to whether a parent is voluntarily unemployed for the purposes of imputing income for child support determinations. Part I demonstrates how multiple judicial officers’ distraction, imagination, and misguided reliance on legal fictions, rather than on the facts of the individual’s life, made injustice real in Kim’s life. It attempts to understand judges’ unarticulated reasoning through a re-created conversation. Part II discusses legal treatment of transgender people in general. Part III suggests legal recommendations to promote clearer thinking and more rational decisions within the courts regarding the distracting and emotionally charged issues surrounding transgender individuals. Specifically, I suggest that the legal fiction that permits courts to impute income to unemployed parents should change to explicitly recognize discrimination in hiring. Courts should adopt an evidentiary rule accepting self-reports of gender identity. To facilitate legal thinking that transcends simplistic binary models of human experience, judges should make an effort to understand more about trans people. Judges should also adopt a simple schema for understanding the distinct categories of sex, gender identity, gender expression, and sexual orientation. Judges should be evaluated according to their ability to prioritize facts (here, discrimination against transgender people in hiring, which leads to unemployment) over legal fictions (here, a parent able to work but not working is voluntarily unemployed, rather than the target of discrimination in hiring). Finally, judges should be evaluated for their ability to prioritize facts over their own fears.